Advisory Jurisdiction of the Iraqi state consultative council and its role in the protection of public rights and freedoms - يونس مها بهجت; جمعة جهاد علي (Journal of Legal Sciences, 2019)
The State Legislative Council practices its consultative specialization through issuing the fatwasand legal opinions for the ministries and the institutions which are not associated with a ministry, The Advisory Commissions with each of General Commission, Presidency Commission and The Specialized Commission take charge of this mission. Where the abovementioned Advisory Commissions practice different jurisdictions in codification field, giving legal opinion field and legal advisory. The State Legislative Council through its Advisory specialization could provide a protection for the rights and general freedomswhere it contributed in protecting the rights and personal freedoms through issuing the fatwas that dictatesto that impermissibleto sequester individuals without Judgement Decision and disable the legislations that issued in the era of the previous regime which granted members intheExecutive authority like ministries and governorsthe authority to sequesterindividuals with an administrative decision , the council also contributed in protecting the rights and intellectual freedoms through its fatwa to respect the religious freedom and teaching right. The council had a role of protecting the rights and economic freedoms issuing many fatwas about the operation of transferring the property and affirming to respect this right through preventing the Head of the Executive authority from issuing administrative decisions of sequestering the individuals real estates without issuing Judgement Decision, the council also contributed with protecting the trade by the fatwa of the permit to establish companies that works in employing workers without the agreement of the sector authority. Finally, the council played a role in protecting the rights and social freedoms through issuing the fatwas that protect the work right and the worker right in getting the suitable wage and other wages like the bonus.